Channel Newsasia : the 'Asian perspective' & its newsroom culture - Haminah Osman (2008)
This study aims to gain a deeper understanding of the thinking that goes into shaping Channel NewsAsia, in particular its news programmes. It seeks to understand how the channel functions from the point of view of its office culture.